Evaluation of adaptive treatment planning for patients with non-small cell lung cancer. (5th May 2017) - Zhong, Hualiang; Siddiqui, Salim M; Movsas, Benjamin; Chetty, Indrin J
Abstract: The purpose of this study was to develop metrics to evaluate uncertainties in deformable dose accumulation for patients with non-small cell lung cancer (NSCLC). Initial treatment plans (primary) and cone-beam CT (CBCT) images were retrospectively processed for seven NSCLC patients, who showed significant tumor regression during the course of treatment. Each plan was developed with IMRT for 2 Gy × 33 fractions. A B-spline-based DIR algorithm was used to register weekly CBCT images to a reference image acquired at fraction 21 and the resultant displacement vector fields (DVFs) were then modified using a finite element method (FEM). The doses were calculated on each of these CBCT images and mapped to the reference image using a tri-linear dose interpolation method, based on the B-spline and FEM-generated DVFs. Contours propagated from the planning image were adjusted to the residual tumor and OARs on the reference image to develop a secondary plan. For iso-prescription adaptive plans (relative to initial plans), mean lung dose (MLD) was reduced, on average from 17.3 Gy (initial plan) to 15.2, 14.5 and 14.8 Gy for the plans adapted using the rigid, B-Spline and FEM-based registrations. Similarly, for iso-toxic adaptive plans (considering MLD relative to initial plans) using the rigid, B-Spline and FEM-based registrations, the average doses were 69.9 ± 6.8, 65.7 ± 5.1 and 67.2 ± 5.6 Gy in the initial volume (PTV1 ), and 81.5 ± 25.8, 77.7 ± 21.6, and 78.9 ± 22.5 Gy in the residual volume (PTV21 ), respectively. Tumor volume reduction was correlated with dose escalation (for isotoxic plans, correlation coefficient = 0.92), and with MLD reduction (for iso-fractional plans, correlation coefficient = 0.85). For the case of the iso-toxic dose escalation, plans adapted with the B-Spline and FEM DVFs differed from the primary plan adapted with rigid registration by 2.8 ± 1.0 Gy and 1.8 ± 0.9 Gy in PTV1, and the mean difference between doses accumulated using the B-spline and FEM DVF's was 1.1 ± 0.6 Gy. As a dose mapping-induced energy change, energy defect in the tumor volume was 20.8 ± 13.4% and 4.5 ± 2.4% for the B-spline and FEM-based dose accumulations, respectively. The energy defect of the B-Spline-based dose accumulation is significant in the tumor volume and highly correlated to the difference between the B-Spline and FEM-accumulated doses with their correlation coefficient equal to 0.79. Adaptive planning helps escalate target dose and spare normal tissue for patients with NSCLC, but deformable dose accumulation may have a significant loss of energy in regressed tumor volumes when using image intensity-based DIR algorithms. The metric of energy defect is a useful tool for evaluation of adaptive planning accuracy for lung cancer patients.